THE INFLUENCE OF TAX PAYMENT AWARENESS AND UNDERSTANDING OF TAX REGULATIONS ON THE LEVEL OF LAND AND BUILDING TAX REVENUE AT THE REVENUE DEPARTMENT AND MANAGEMENT SURABAYA CITY FINANCE - Indriyani Lintiyaningrum; Tjandra Wasesa; Diana Zuhro; Sutini; Wiratna; Heri Toni; Hendro Pranoto; Achmad Daengs GS (PT. Mawadaku Sukses Solusindo, 2023)
In financing regional development, tax is an alternative source of financing needed by the government, including land and building tax. Land and Building Tax is the only property tax in Indonesia and has increased from year to year. Apart from that, Land and Building Tax has the largest number of taxpayers compared to other taxes. Even though Land and Building Tax has a broad impact, the proceeds from Land and Building Tax are returned to the regions concerned for the implementation and improvement of development in their respective regions. The aim of this research is to determine the influence of the level of awareness of tax payments and understanding of tax regulations for individual taxpayers, both partially and simultaneously, on land and building tax revenues in the work area of ​​the Rungkut Kidul Subdistrict Office. The population is all effective taxpayers registered in the working area of ​​the Rungkut Kidul Subdistrict Office. The sample used was 95 individual taxpayers for land and building tax. The sampling technique used purposive sampling, namely random sampling of 95 respondents. The analysis technique used is multiple linear regression.